Temporal changes in grain yield and quality of rice varieties released in Guangdong Province, China (1990–2020) - Yang, Huifang; Wu, Longmei; Zhang, Bin; Yang, Taotao; Zou, Jixiang (Frontiers in Agronomy, 2025)
IntroductionOver the past three decades, Guangdong Province has released numerous rice varieties, but comprehensive analyses of their yield and quality characteristics remain limited.MethodsThis study systematically evaluated a total of 982 rice varieties released in Guangdong Province from 1990 to 2020, focusing on grain yield, yield components, and quality parameters.Results and discussionThe results revealed that the number of inbred rice varieties was significantly lower than that of hybrid rice varieties, while the number of high-quality late rice varieties was greater than that of high-quality early rice varieties. Temporal analysis showed significant increases in the release of inbred rice, hybrid rice, and high-quality hybrid late rice varieties. Hybrid rice demonstrated superior grain yield (6.98 t hm−2) compared to inbred rice (6.50 t hm−2), which was primarily attributable to enhanced spikelet per panicle and grain weight. Both inbred and hybrid rice exhibited significant yield improvements over time, driven by increases in spikelet per panicle, filled grain percentage, or grain weight. Notably, the panicle number of both inbred and hybrid rice displayed a significant declining trend. Quality analysis indicated that inbred rice surpassed hybrid rice in head rice rate and chalkiness, while late rice outperformed early rice in these parameters. Early rice exhibited higher gel consistency but lower amylose content compared to late rice. However, both inbred and hybrid rice showed declining trends in head rice rate, chalkiness, and amylose content over the study period. In the future, rice breeding strategies in Guangdong should focus on improving spikelet per panicle and grain weight in inbred rice, and enhancing panicle number in both inbred and hybrid rice varieties to achieve further yield improvement. Furthermore, the development of new varieties should prioritize higher head rice rate, particularly for early rice. These findings provide crucial insights into the evolving patterns of grain yield and quality in Guangdong Province, offering valuable guidance for future breeding strategies and cultivation practices.